MANUFACTURING COMPANY BANKRUPTCY PREDICTION IN INDONESIA WITH ALTMAN Z-SCORE MODEL - Matturungan, Nur Hasbullah; Purwanto, Budi; Irwanto, Abdul Kohar (Universitas Brawijaya, Indonesia, 2017)
Model Altman is one of the models used to predict financial distress. Some of the results of research that conducted in Indonesia showed that Altman model is completely accurate in predicting financial distress but the other found the opposite results. This inconsistency indicates the need to adapt the model by checking whether variables affect Altman model in financial distress companies in Indonesia and the adjustment coefficients Altman to be able to better predict about financial distress. The results showed that the partial test working capital/total assets, retained earnings to total assets, and earning before interest and tax to total assets were able to classify the company's financial distress. However, the model that formed by five variables were able to classify financial distress well with an accuracy of 87.8%.